2017
DOI: 10.3390/ijerph14070783
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Daily Mobility of Adults in Peri-Urban South India

Abstract: Daily mobility, an important aspect of environmental exposures and health behavior, has mainly been investigated in high-income countries. We aimed to identify the main dimensions of mobility and investigate their individual, contextual, and external predictors among men and women living in a peri-urban area of South India. We used 192 global positioning system (GPS)-recorded mobility tracks from 47 participants (24 women, 23 men) from the Cardiovascular Health effects of Air pollution in Telangana, India (CHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…Sex-specific (or gender-specific) effects of air pollution are often determined by differences in time–activity patterns. In the study population, women spend the majority of their time near home (83% of the daytime vs. 57% for men) 35. This suggests that residence-based exposure estimates may be more relevant for women than for men in this setting, and may explain why we observed stronger associations between PM 2.5 and BP in women.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Sex-specific (or gender-specific) effects of air pollution are often determined by differences in time–activity patterns. In the study population, women spend the majority of their time near home (83% of the daytime vs. 57% for men) 35. This suggests that residence-based exposure estimates may be more relevant for women than for men in this setting, and may explain why we observed stronger associations between PM 2.5 and BP in women.…”
Section: Discussionmentioning
confidence: 81%
“…We identified potential confounders using prior evidence and bivariate associations with the outcome and/or the exposure, as illustrated using DAGitty 2.3 34 in a directed acyclic graph (eFigure 2). Given the importance of sex as a determinant of baseline health status, socio-economic and lifestyle factors, and time-activity patterns influencing residential exposure,35 we decided a priori to stratify all analysis by sex, but we also report results for the whole study population. We excluded participants with missing data on sex (n=5), household ID (n=82), BP (n=3), and land-use regression-predicted estimates (n=580).…”
Section: Methodsmentioning
confidence: 99%
“…Mobility patterns and activities are notably different between men and women in this population ( Sanchez et al, 2017 ). In a prior work based on GPS tracking in the same study population, we reported that men typically spend less time in the home, make more trips at high speed (e.g., in vehicle rather than walking), and travel further distances from the home compared to women ( Sanchez et al, 2017 ). Nonetheless, our results here did not identify travel microenvironments as contributing to high short-term PM 2.5 exposure for either sex.…”
Section: Discussionmentioning
confidence: 98%
“…Analyses using the wearable camera-derived microenvironmental information mostly cover the 7 am–8 pm interval. All analyses were stratified by sex, which was strongly associated with activity patterns in our study population ( Sanchez et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Associations were stronger in women than in men, possibly because women in this region tend to spend more time at home than men. 7 Tonne says most of the evidence connecting cardiovascular health with surrounding green space comes from studies in the United States and Europe, 8 whereas comparable evidence from low-and middle-income countries is lacking. The results from her study, she says, show evidence of the pattern in a developing world setting-"Not all the associations are statistically significant, but they're going in the direction we expected."…”
Section: Science Selectionmentioning
confidence: 99%